Two Proposals for a Semiotic Taxonomy of Fake News and Deepfakes - Piero Polidoro (Actes Sémiotiques)
The paper proposes a semiotic taxonomy of fake news and deepfakes, phenomena that, while rooted in contemporary media practices, raise fundamental questions about discursive norms, acts of enunciation, and conditions of veridiction. Through critical comparison with some existing taxonomic models, the essay develops a theoretical-operational grid based on the main variables of expression and content, cross-referenced with types of communicative situations that bring into play awareness and the enunciative relationship between actors. The work is in the vein of the reflection proposed by this issue, interpreting fake news, and with them the cases of deepfakes, as deviant normative devices capable of reshaping collective expectations about the textual forms of veridiction. The aim is to contribute to a semiotics of norms that, from communicative pathologies, clarifies the structure and function of discursive constraints in digital interactions.